The influence of DISI engine control parameters and M15 fuel on regulated and particulate emissions under light-load. (15th September 2020) - Feng, Shuang; Hong, Wei; Li, Xiaoping; Xie, Fangxi; Su, Yan
Abstract: Regulated and particulate emissions on a four-cylinder direct-injection spark ignition (DISI) engine fueled with methanol-gasoline blended (M15-15% of methanol by volume in gasoline) were compared with gasoline at speed of 1500 r/min, 2500 r/min and the injection quantity of each cycle is 47 mg/cycle. The effect of ignition timing, injection timing, injection pressure and excess air ratio on regulated emissions (HC, CO, and NOx ), particle number (PN) emissions and brake thermal efficiency were investigated experimentally. The results show that NOx emissions increased with the injection timing advanced, meanwhile, there is an optimal injection timing for the lowest HC and CO emissions. When the ignition timing is advanced, all the regulated emissions increased, but there is only slight impact on the HC and CO emissions. Lean mixture (the excess air ratio range from 1 to 1.2) is beneficial to HC, CO and particulate emissions. Higher fuel injection pressure makes HC, CO emissions reduced while NOx increased little. When the injection timing is 270°CA BTDC, it is suitable for making an ideal mixture for the best control of particulate emissions. Retarding ignition timing, use of lean mixture or improved fuel injection pressure will all reduce PN emissions effectively. Compared with gasoline, M15 has less regulated and PN emissions, and it has higher brake thermal efficiency.